Spin quenching assisted by a strongly anisotropic compression behavior in MnP. (5th February 2018) - Han, Fei; Wang, Di; Wang, Yonggang; Li, Nana; Bao, Jin-Ke; Li, Bing; Botana, Antia S; Xiao, Yuming; Chow, Paul; Chung, Duck Young; Chen, Jiuhua; Wan, Xiangang; et al.
Abstract: We studied the crystal structure and spin state of MnP under high pressure with synchrotron x-ray diffraction and x-ray emission spectroscopy (XES). MnP has an exceedingly strong anisotropy in compressibility, with the primary compressible direction along the b axis of the Pnma structure. XES reveals a pressure-driven quenching of the spin state in MnP. First-principles calculations suggest that the strongly anisotropic compression behavior significantly enhances the dispersion of the Mn d -orbitals and the splitting of the d -orbital levels compared to the hypothetical isotropic compression behavior. Thus, we propose spin quenching results mainly from the significant enhancement of the itinerancy of d electrons and partly from spin rearrangement occurring in the split d -orbital levels near the Fermi level. This explains the fast suppression of magnetic ordering in MnP under high pressure. The spin quenching lags behind the occurrence of superconductivity at ∼8 GPa implying that spin fluctuations govern the electron pairing for superconductivity.